Institutionalized corruption: power overconcentration of the First-in-Command in China - Jianming, Ren (Crime, law and social change, 2008)
Among various kinds of corruption in China, corruption of the First-in-Command (FIC) is most pernicious, threatening the legitimacy of the Chinese Communist Party and the stability of the state. This paper examines several specific institutional arrangements under China’s current political structure, including the people’s congress, the ruling party system, and the collective leadership team system, to see how they have contributed to power overconcentration in the hands of FICs. This is done in a two-round process: first through the collective leadership team and then by the gestating decision-making rule. The paper also assesses four institutional innovations designed to prevent FIC corruption.